2009
DOI: 10.1111/j.1464-5491.2009.02770.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing amputation rates in patients with diabetes—a population‐based study

Abstract: There has been a significant reduction in the incidence of major lower extremity amputation in patients with diabetes over the 7-year period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
47
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 23 publications
9
47
0
1
Order By: Relevance
“…Our incidence for lower extremity amputation of 1.4 per 10 000 population falls in the middle range of a 10-centre study [10]. Our diabetes-related amputation rate of 0.9 per 10 000 population is much less that the rates if 2.8-43.9 per 10 000 population in one review from the 1990s [11] and less than diabetes-related rates found in Scotland (1.5 per 10 000 in 2006, in a population with diabetes prevalence of 3.8%) [12], even though the prevalence of diabetes is likely to be higher in Lebanon (13.7% in 1995) [13]. In a previous study, differences in the known prevalence of diabetes did not account for the differences in overall amputation rates between centres [10].…”
Section: Incidencementioning
confidence: 84%
“…Our incidence for lower extremity amputation of 1.4 per 10 000 population falls in the middle range of a 10-centre study [10]. Our diabetes-related amputation rate of 0.9 per 10 000 population is much less that the rates if 2.8-43.9 per 10 000 population in one review from the 1990s [11] and less than diabetes-related rates found in Scotland (1.5 per 10 000 in 2006, in a population with diabetes prevalence of 3.8%) [12], even though the prevalence of diabetes is likely to be higher in Lebanon (13.7% in 1995) [13]. In a previous study, differences in the known prevalence of diabetes did not account for the differences in overall amputation rates between centres [10].…”
Section: Incidencementioning
confidence: 84%
“…Several studies in the US and western Europe in recent years have reported decreasing incidence of LEAs in DM populations particularly in response to implementation of improved diabetes foot care (Krishnan et al, 2008;Schofield et al, 2009). In the 5 year longitudinal study by Canavan et al (2008), the incidence rate of LEA in persons with DM dropped from 310.5 per 100,000 persons to 75.9 per 100,000.…”
Section: Diabetic Foot Ulcers and Lower Extremity Amputationmentioning
confidence: 99%
“…A sustained reduction in diabetes‐related lower limb amputation was observed after the institution of job‐planned multidisciplinary secondary care diabetic foot clinics 13, 14, 15, while an earlier report showed a continued high amputation incidence over a decade where no restructuring of services was undertaken 16. Diabetes foot care services in England are commissioned by Clinical Commissioning Groups (CCGs).…”
Section: Introductionmentioning
confidence: 99%